Multi-criteria analysis for selection of priority management programs for the Japaratuba River Basin, SE, Brazil - Carla Z. A. dos Santos; Talitha S. C. Bezerra; Alceu Pedrotti; Arisvaldo V. Méllo Júnior; Laura J. Gomes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The Japaratuba River Basin (JRB), located in Sergipe, Brazil, has accelerated economic development due to oil exploration and an increase in the sugarcane and corn monocultures. Thus, environmental degradation has increased in the basin. Given the importance of the water supply that the hydrographic basin has for the state of Sergipe, and the need to balance its economic growth with environmental conservation, this study had the objective to analyze the Japaratuba River Basin Plan (JRBP), published in 2015, and propose the priority scale for the execution of programs arranged under the scope of a Strategic Environmental Assessment (SEA). Thus, the multi-criteria decision analysis (MCDA) applying the Analytic Hierarchy Process method (AHP) was used with data collection (water supply and distribution, sanitation, and forest cover) for the years 2018, 2019, and 2020, associating Geoprocessing techniques. It was verified that among the criteria analyzed for the definition of the priority scale, those associated with the restoration of ecosystems, sanitation, and hygiene, and water quality were the ones with the highest priority for execution according to the levels of criticality observed. The multi-criteria analysis expands the context of environmental criteria to be observed in further reviews of the JRBP; and expands the strategic environmental vision in the integrated management processes of the basin.